Marxist point of view on migration, consumption, and class: in the perspective of Islamic teachings - Mahmood, Tariq; Ushama, Thameem (The Islamia University of Bahawalpur, Pakistan, 2025)
This paper has been written about migration and the consumption culture in the society and the country. The purpose of this paper is to describe the different aspects of migration, i.e. political, economic, social and cultural on the origin home country and on the country in which the persons are migrated. No doubt, employment is considered the biggest purpose of migration. Besides this, education and training also has the strong objective of migration. And these are affecting and playing a key role in the economy of the original home country and also in the economy of the migrated country. Effects of migration may be positive and negative also. Its positivity and negativity depends upon the ability and role of migrants. Because of migrants, shortage of goods occurs due to increased population( migrants), demand for goods increases. Therefore, as a result of increased demand and shortage or fixed supply, prices of goods hike. Furthermore, the country from which people migrate, and if they are educated and skillful, their home country has to bear loss in real terms, that is, shortage of educated and technical experts and brain drain , while foreign remittances may be increased because of sending money to the home country. Besides this, the effects of migration on family life in absence of migrants can't be ignored. Especially in those families, where the only male person has been migrated while the children are under the teen ages or in the teen ages, their chances to flee from education increases than those whose heads are not migrated. In short, this paper presents the Marxist point of view and Islamic teachings’ point of view regarding migration, consumption and labour in very brief manner.